Sinkronisasi Regulasi tentang Hak Ekonomi Anak di Indonesia dengan Convention on The Rights of The Child/Synchronization of Regulations on Children's Economic Rights in Indonesia with the Convention on The Rights of The Child - Usman, Moh (De Jure: Jurnal Hukum dan Syari'ah, 2020)
Abstract: Children are the next generation who must be given protection by parents, society and the state. Various regulations were formulated to ensure the fulfillment of children's rights. However, various regulations regarding the guarantee of children's rights often lead to legal disharmony. This article aims to describe the synchronization of regulations on the maintenance of the economic rights of children in the family, particularly with the Convention on The Rights of The Child. This article is derived from doctrinal legal research using statutory regulations and conceptual approaches. The results of this study indicate that the material contained in several laws in Indonesia is in line with the Convention on the Rights of the Child, such as the amount of material for children's economic maintenance rights. Even so, there are still regulations that are not synchronized, for example with regard to limits on children's economic maintenance and allowing parents to take children's assets.Keywords: children's rights; family; Constitution.Anak merupakan generasi penerus yang harus diberikan perlindungan oleh orang tua, masyarakat, dan negara. Berbagai regulasi dirumuskan untuk menjamin terpenuhinya hak-hak anak. Namun, berbagai regulasi tentang jaminan hak-hak anak tidak jarang menimbulkan disharmoni hukum. Artikel ini bertujuan mendeksripsikan sinkronisasi regulasi pemeliharaan hak ekonomi anak dalam keluarga, khususnya dengan Convention on The Rights of The Child. Artikel ini berasal dari penelitian hukum doktrinal dengan pendekaran peraturan perundang-undangan dan pendekatan konsep. Hasil dari penelitian ini menunjukkan bahwa materi yang terkandung dalam beberapa perundang-undangan di Indonesia sudah sejalan antara Konvensi Hak Anak, seperti besaran materi hak pemeliharaan ekonomi anak. Meskipun demikian, masih terdapat regulasi yang belum sinkron, misalnya berkaitan dengan batas pemeliharaan ekonomi anak dan diperbolehkannya orang tua mengambil harta anak.Kata Kunci: hak anak; keluarga; undang-undang.